Effects of Light Spectra on Nutritional Composition in Juvenile Sinonovacula constricta (Lamarck 1818) and Transcriptomic Analysis - Mengqi Zhang; Fei Kong; Deshui Chen; Xiaojun Yan; Zhaoshou Ran; Jilin Xu (Aquaculture Nutrition)
The razor clam Sinonovacula constricta, a commercially important and nutritionally valuable bivalve species, has been found to display notable responses to different light spectra. While previous research has highlighted the influence of light spectra on the growth, feeding rate, and various physiological characteristics of S. constricta, its impact on the biochemical composition of this species remains unclear. Herein, we investigated the proximate, fatty acid, and amino acid compositions of S. constricta cultured under various light spectra, including white, violet, blue, cyan, green, yellow, red, and darkness. Furthermore, we explored the potential molecular mechanisms underlying these observations through transcriptomic analysis. The results indicate that the light spectrum has a significant impact on the growth, biochemical composition, and gene expression of juvenile S. constricta. Specifically, culturing S. constricta under the yellow light led to improved growth rate (1.09 ± 0.03%/day), higher levels of carbohydrate (26.27% ± 0.49%), crude lipid (11.99% ± 0.23%), energy contents (14,611.34 ± 1,067.01 kJ/kg), and essential amino acids (15.22 ± 0.01 g/kg), as well as increased proportions of polyunsaturated fatty acids (12.38 ± 0.31 µg/mg). These findings suggest that yellow light may play a crucial role in enhancing the nutritional quality of S. constricta. Moreover, the transcriptomic analysis revealed that the yellow light treatment upregulated pathways related to fatty acid biosynthesis, glycine, serine, and threonine metabolism and fatty acid metabolism. This indicates that yellow light may influence nutrient metabolism regulation in S. constricta, potentially leading to the observed changes in biochemical composition. Overall, our study recommends cultivating juvenile S. constricta under yellow light to optimize their growth and nutritional value. Further research could delve deeper into the molecular mechanisms underlying the effects of different light spectra on S. constricta to enhance our understanding of how light influences aquaculture practices and the nutritional quality of seafood products.